Selectively localized: Temporal and visual structure of smartphone screen activity across media environments. (September 2022) - Muise, Daniel; Lu, Yingdan; Pan, Jennifer; Reeves, Byron
This study demonstrates how localization and homogenization can co-occur in different aspects of smartphone usage. Smartphones afford individualization of media behavior: users can begin, end, or switch between countless tasks anytime, but this individualization is shaped by shared environments such that smartphone usage may be similar among those who share such environments but contain differences, or localization, across environments or regions. Yet for all users, smartphone screen interactions are bounded and guided by nearly identical smartphone interfaces, suggesting that smartphone usage may be similar or homogenized across all individuals regardless of environment. We study homogenization and localization by comparing the temporal, visual, and experiential composition of screen activity among individuals in three dissimilar media environments—the United States, China, and Myanmar—using one week of screenshot data captured passively every 5 s by the novel Screenomics framework. We find that overall usage levels are consistently dissimilar across media environments, while metrics that depend more on moment-level decisions and user-interface design do not vary significantly across media environments. These results suggest that quantitative research on homogenization and localization should analyze behavior driven by user interfaces and by contextually determined parameters, respectively.